Exemplary series and Christian typology: modelling on sainthood in Damascus. (May 2015) - Bandak, Andreas; BANDAK, ANDREAS; HØJER, LARS
<x xml:space="preserve">Abstract</x> In this paper, I explore the way in which examples are used in sermons among the pious followers of Our Lady of Soufanieh in Damascus, Syria. In the sermons, a particular logic of seriation functions to present specific models and exemplars as prisms of lives to be imitated. The framing of these lives takes place through entextualizations, whereby the life of some is made into texts that others are told to emulate. The process of making life into text and text into life is explored in the production of examples at the weekly Saturday sermons in Soufanieh. While directly related to life as lived, such sermons also stand for a broader class of life as forma vitae, that is, lives to be followed. I thus explore the example as exemplum, a particular moral story used for edification and didactic purposes, one which situates the listener at the centre of the story by integrating the miraculous happenings in Soufanieh with the response of the individual. The sermons thus serve to examine exemplification and the modelling of sainthood in Damascus in the years preceding the current civil war.